Territorialidades da agricultura orgânica em Marechal Candido Rondon, PR. - Burin, Jane Carla (2010)
The Territory consists of inumerous territorialities settling a function of the internal and external, natural, social, political and economic interaction. The organic agriculture is an area under construction in the municipality of Marechal Cândido Rondon, being able to reorganize the rural areas and their surroundings. By fall rescues cultural and social values, reinforces notions of sustainability, provides mechanisms that boosts the local economy. However, to be effectively implemented the process needs a network of relations and a link between public policies, organizations and farmers. The main objective of this study is to understand the interrelationships that take place within the organic agriculture and the formation of territoriality. The municipality of Marechal Cândido Rondon is located in the west midland region of Parana, in the microregion of Toledo. For this work, the authors who address the family farming and organic were consulted, beyond the concept of territory and territoriality and role of organizations in regional / local development to support the theoretical discussions of the results. The methodology is based on theoretical research, consultation of bibliographies that guide the proposed themes and data collection. These data were obtained through field research among organizations involved with organic agriculture and farmers, through pre-arranged visits, lectures in local documents, images record and qualitative data. In discussing the results it was concluded that organic farming is present in the city since 1960, but in 1990 it takes a larger proportion towards the emergence of organizations like the Central Association of Ecological Producers and the Capa nucleus. The efforts by these organizations and others as Emater, City Hall, Unioeste and Itaipu make glimpse new possibilities for organic agriculture in the municipality of Marechal Cândido Rondon.